2003
DOI: 10.1021/ac034594a
|View full text |Cite
|
Sign up to set email alerts
|

Mass Distribution Measurement of Water-Insoluble Polymers by Charge-Reduced Electrospray Mobility Analysis

Abstract: 1-Methyl-2-pyrrolidone (NMP) seeded with 5% trifluoroacetic acid is identified as a singular buffer, polar enough to produce fine electrospray drops, yet having excellent solubility for many industrial polymers such as polystyrene (PSR) and poly(methyl methacrylate) (PMMA). Four PSR mass standards (M = 9.2, 34.5, 68, and 170 kDa) with narrow mass distributions are electrosprayed from their solutions in this buffer. The high charge on the resulting ions is reduced to unity with a radioactive source, whereby the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Polyethylene glycols (PEGs) in the size range of 4k to 700 kDa were used to establish that molecular weight and mobility diameter could be correlated by a one-third power law [47] a correlation that had already been established for proteins three years prior [11]. Similar behavior has been reported for water insoluble polymers [48]. Using this correlation, ES-DMA can also been used to determine density of polymers (or proteins) [11,49].…”
Section: 2polymers and Proteinsmentioning
confidence: 71%
See 2 more Smart Citations
“…Polyethylene glycols (PEGs) in the size range of 4k to 700 kDa were used to establish that molecular weight and mobility diameter could be correlated by a one-third power law [47] a correlation that had already been established for proteins three years prior [11]. Similar behavior has been reported for water insoluble polymers [48]. Using this correlation, ES-DMA can also been used to determine density of polymers (or proteins) [11,49].…”
Section: 2polymers and Proteinsmentioning
confidence: 71%
“…A simple method of passivating capillaries with BSA and gelatin was presented a coverages of these proteins onto ES capillaries were also quantified in situ using the ES-DMA. Although in the ES-mass spectrometry community it is fairly common to passivate capillaries with polyethylene glycols (PEGs) [48] this is the first time that passivation for ES-DMA has been systematically explored. It was also found that gelatin passivated capillaries are effective in reducing non-specific adsorption of immunoglobulins and are stable upto about 3 days within a pH range of 4.8 to 9.0 although gelatin desorption was observed at low pH (≈ 2.1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the reasons for the differences in the determined size values found in this study are, it is obvious that the use of calibrants of known size, molecular mass and high structural homogeneity (monodisperse) are absolutely necessary for each individual instrument even in case of identically constructed devices. The use of calibration compounds such as proteins, polymers or inorganic particles, are indispensable for the precise functioning of any nDMA system, especially in case of the analytical task of molecular mass determination (the nDMA system is used as 'mass spectrometer' at ambient pressure [4,15]) or in which conclusions about size, changes of size caused by agglomeration, denaturation, degradation or the formation of complexes of certain analytes have to be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with charged particle or molecular ion generation from liquid samples with nano-electrospray sources [6,7] (n-ES) and subsequent neutralization of the highly charged species [8][9][10], this method has already been successfully applied in analysing important biochemical analytes, such as viruses and virus fragments [4,11], bacteriophages, DNA [12], proteins and protein complexes [4,13], as well as synthetic materials, such as polyethylene glycol polymers [14], polystyrene [15], PAMAM dendrimers [16] and nanometer sized silica particles [17].…”
Section: Introductionmentioning
confidence: 99%